THE INFLUENCE OF COMMUNICATION IN SEX EDUCATION ON 2022 STAMBUK COMMUNICATION SCIENCE STUDENTS AT STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA TO REDUCE THE NUMBER OF CASES OF FREE SEX - Hardiansyah, Tubagus Rizki; Nasution, Syawaluddin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
This research investigates the influence of communication in sex education on 2022 standard Communication Science students at UIN North Sumatra in the context of reducing the number of cases of casual sex. This approach integrates communication theories such as information reception and processing theory, interpersonal communication, and persuasive communication theory to understand how communication influences students' sexual understanding and behavior. The results of statistical analysis using the T test and simple regression show that communication in sex education has a significant and positive influence in reducing cases of casual sex among students. This research offers deep theoretical insights and practical implications in designing effective sexual education programs in Islamic academic settings.